Impact of electrolyte intercalation on the corrosion of graphene-coated copper. (March 2015) - Wlasny, I.; Dabrowski, P.; Rogala, M.; Pasternak, I.; Strupinski, W.; Baranowski, J.M.; Klusek, Z.
Highlights: Corrosion in graphene-coated copper mono- and polycrystals is investigated. Graphene-coated copper monocrystal shows no traces of corrosion. Copper oxides can be found on copper foil coated with graphene. Corrosion is enabled in copper foil due to electrolyte intercalation at interface. Abstract: The protection offered by graphene to copper mono- and polycrystals is studied. Cu(1 1 1) surface shows no traces of corrosion products due to the graphene coating. At the same time copper oxides are found on the copper polycrystalline foil despite the protection due to electrolyte intercalation at the graphene/copper interface. However, the amount of corrosion products is still lower in this case than in non-protected copper. The quantitative analysis of corrosion processes are based on XPS and AES spectra of non-coated and coated copper single and polycrystals. We evaluate graphene as a protection against corrosion in regard to industrial applications.